2009
DOI: 10.1242/jcs.048975
|View full text |Cite
|
Sign up to set email alerts
|

The NIMA-family kinase Nek3 regulates microtubule acetylation in neurons

Abstract: NIMA-related kinases (Neks) belong to a large family of Ser/Thr kinases that have critical roles in coordinating microtubule dynamics during ciliogenesis and mitotic progression. The Nek kinases are also expressed in neurons, whose axonal projections are, similarly to cilia, microtubule-abundant structures that extend from the cell body. We therefore investigated whether Nek kinases have additional, non-mitotic roles in neurons. We found that Nek3 influences neuronal morphogenesis and polarity through effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 77 publications
1
51
0
Order By: Relevance
“…The localization of exogenous NEK3 proteins were visualized by staining PRL-stimulated MCF-7 cells with ␣-V5 antibodies (red) and was found to be predominantly cytoplasmic (Fig. 6D), which is consistent with previously published reports in both fibroblasts (29) and neurons (30). No differences in NEK3 localization were observed between wild-type NEK3 and the phospho-mutants (NEK3-T161V or NEK3-T165V), which all showed enriched staining at the cell periphery and strong co-localization with actin in membrane ruffles (Fig.…”
Section: Journal Of Biological Chemistry 21397supporting
confidence: 91%
See 1 more Smart Citation
“…The localization of exogenous NEK3 proteins were visualized by staining PRL-stimulated MCF-7 cells with ␣-V5 antibodies (red) and was found to be predominantly cytoplasmic (Fig. 6D), which is consistent with previously published reports in both fibroblasts (29) and neurons (30). No differences in NEK3 localization were observed between wild-type NEK3 and the phospho-mutants (NEK3-T161V or NEK3-T165V), which all showed enriched staining at the cell periphery and strong co-localization with actin in membrane ruffles (Fig.…”
Section: Journal Of Biological Chemistry 21397supporting
confidence: 91%
“…To this end, key catalytic residues within the kinase domain of NEK3 were mutated by site-directed mutagenesis (D145A and K33R/D127A), which were predicted to render the protein kinase-inactive based upon homology to mouse NEK3 (29,30) or other human NEK kinases (31,32). Kinase-inactive NEK3 mutants were then subjected to in vitro autophosphorylation assays (Fig.…”
Section: Identification Of Nek3 Autophosphorylation Activity Inmentioning
confidence: 99%
“…To this effect, it has been shown that Nek7 accelerates microtubule dynamic instability during interphase (22) and that it is able to phosphorylate ␣-and ␤-tubulin in vitro (23). Moreover, it has been demonstrated that the related family member Nek3 is able to control microtubule acetylation (24). Consequently, in light of the aforementioned study linking microtubule acetylation and Nlrp3 inflammasome signaling, we wondered whether Nek7 was involved in microtubule acetylation during Nlrp3 inflammasome activation.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed above, for polarized epithelial cell migration, Paxillin binds to HDAC6 and stimulates microtubule acetylation [128]. Moreover, expression of two phosphorylation-defective mutants of NIMA (never in mitosis A)-related kinase 3 (NEK3) decreases tubulin acetylation, reduces neuronal polarity and alters cell morphology [134]. Pharmacological inhibition of HDAC6 reverses this effect [134], suggesting that through tubulin deacetylation, HDAC6 modulates neuronal polarity.…”
Section: Tubulin Acetylation and Intracellular Transportmentioning
confidence: 99%